Wind energy engineering : a handbook for onshore and offshore wind turbines - Letcher, T. M. (Academic Press, 2017)
This book provides current research-focused text on all aspects of wind energy engineering, including the present state of wind integration and distribution worldwide, assessment of the advances in turbine technology, and how the investment, planning, and economic infrastructure can support those innovations. It also provides analysis of the latest high-level research and explores real world application potential in relation to the developments.